Mapping Tolerance in Accounting and Finance: A Decade of Behavioral Insights and Research Trends (2013–2023) - Sunitha Devi; I Ketut Yadnyana; Anak Agung Gde Putu Widanaputra; Ni Made Dwi Ratnadi (Universitas Pendidikan Ganesha, 2025)
Tolerance, understood as an individual psychological disposition, plays a vital role in mitigating conflicts, particularly those rooted in financial and accounting contexts. Despite its significance, most existing research tends to focus on institutional mechanisms such as corporate governance, financial reporting quality, and risk tolerance related specifically to investment behavior, rather than exploring how individual tolerance as a broader construct influences conflict prevention within financial domains. This gap highlights the need for a comprehensive examination of tolerance from an individual behavioral perspective in accounting and finance. This study aims to address this gap by conducting a Systematic Literature Review (SLR) of 29 empirical studies published between 2013 and 2023, all retrieved from the Scopus database. The analysis encompasses demographic trends, thematic emphases, and methodological approaches within the current literature. Key findings from the demographic analysis indicate a surge of interest during the COVID-19 pandemic period (2020–2021), suggesting heightened relevance of tolerance in times of crisis. Furthermore, the majority of relevant studies are published in specialized accounting and finance journals, with a geographic concentration in Asian countries such as Malaysia, Indonesia, China, and Korea. Quantitative research methods dominate these studies, focusing predominantly on risk tolerance rather than broader tolerance behaviors. The review identifies a diverse array of factors affecting individual tolerance, including demographic variables (age, gender, marital status, ethnicity, education), personality traits (openness, prudence, honesty, humbleness), and socio-cultural influences (culture, politics, family support, religion). Tolerance influences various behavioral outcomes, ranging from investment decision-making and financial risk management to the use of online social networks and even academic fraud conduct. By synthesizing these findings, the study contributes meaningful insights to the emerging fields of financial behavior and accounting behavior, emphasizing the critical, yet underexplored, role of tolerance. Additionally, the mapping of literature highlights promising directions for future research to further elucidate how fostering tolerance can effectively reduce conflicts in financial settings.